The call of the wild [videorecording (DVD)] - Gillan, Karen, 1987-; Ford, Harrison, 1942-; Whitford, Bradley; London, Jack, 1876-1916 (20th Century Fox, 2020)
Adapted from the beloved literary classic, this film is the story of Buck, a big-hearted dog whose blissful domestic life is turned upside down when he is suddenly uprooted from his California home and transplanted to the exotic wilds of the Alaskan Yukon during the Gold Rush of the 1890s. As the newest rookie on a mail delivery dog sled team, and later its leader, Buck experiences the adventure of a lifetime, ultimately finding his true place in the world and becoming his own master.